Formulation of a Surf-Similarity Parameter to Predict Tsunami Characteristics at the Coast - Roubos, Jochem; Glasbergen, Toni; Hofland, Bas; Bricker, Jeremy; Zijlema, Marcel; Esteban, Miguel; Tissier, Marion (Journal of Coastal and Hydraulic Structures, 2021)
To calculate tsunami forces on coastal structures it is of great importance to determine the shape of the tsunami front reaching the coast. Based on literature reviews, analytical reasoning, video footage, and numerical modelling it is concluded that both the continental shelf slope and the bay geometry have a significant influence on the transformation of a tsunami wave near the coastline. After conducting 1D and 2DH wave simulations, a distinction is made between three types of tsunami waves; a non-breaking front (surging), a breaking front and an undular bore breaking front. Tsunami waves transform into these three wave types over a steep continental shelf, an intermediate sloped continental shelf, and a gentle sloped continental shelf, respectively. A new tsunami surf-similarity parameter is proposed to quantitatively predict the type of wave at the coastline, which was validated based on observations during the 2011 Tohoku Earthquake and Tsunami.